(untitled) (Research, Society and Development, 2021)
This study aims to present the experiences lived by a Physical Education Professional (PEF) in the exercise of their functions in a team of Consultório na Rua (CR). It is an experience report, about the experiences of a Multiprofessional resident PEF in Mental Health while working at the RC in Aracaju/Sergipe/Brazil, between August 2019 and February 2020. For data collection, participant observation with the data being prepared in a field diary. We identified situations of prejudice and discrimination on the part of society regarding the homeless population; difficulties in accessing the Health Care Network (RAS); extreme social vulnerability and notorious gaps between public health policies and their applicability. The importance of the work of the CoR team was verified - a work of care and assistance developing actions integrated with the services of the SAN. In addition, the relevance of the insertion of the PEF in the CR is highlighted as an agent that acts from the perspective of comprehensive care, developing health promotion strategies beyond its specificity core. Furthermore, it acts in the face of the different health problems and needs of that population, including the active search for users who drugs, also contributing to the realization of matrix support, reception, health education, intersectoral articulation and strategies harm reduction. Therefore, the Residence, becomes a powerful strategy to provide teaching and learning processes with a view to continuing education.